Rancang Bangun Sistem Informasi Skripsi Daring Berbasis WEB (Studi Kasus : Jurusan Teknik Informatika, Universitas Papua) - Karubaba, Getreda Gabrilla; Yuliawan, Kristia (ScientiCO : Computer Science and Informatics Journal, 2018)
The application made in this study is used in the scope of the University of Papua Informatics Engineering Department, based on information and procedures for making the final thesis task of the Informatics Engineering Department of the University of Papua, this application was made using the Waterfall system development model and developed with PHP programming language with a CodeIgniter framework and MySQL Database. This Online Thesis application consists of 3 users. The first user in this application is the Chair of the Study Program who acts as the Administrator, the second is Thesis Supervisor, and The third is Students of the Informatics Engineering Department at the University of Papua. Available menu options are Upload Proposal, List of Proposals, Thesis Title List, Message, New Message, Inbox, Control Card Menu, Student List, Lecturer List, and Profile. Information System that can facilitate the search for proposals, thesis titles and guidance processes carried out by the Informatics Engineering Department of the University of Papua.Â